Removal and insertion of central venous catheters in cancer patients is associated with high symptom burden. (3rd August 2018) - Raad, Sammy; Chaftari, Anne Marie; Hachem, Ray Y; Shah, Pankil; Natividad, Elizabeth; Cleeland, Charles S; Rosenblatt, Joel
ABSTRACT: Objectives : To assess the symptom burden associated with CVC removal and insertion in cancer patients. Methods : We collected patient-reported symptom-burden outcomes for 60 consecutive cancer patients: 30 undergoing CVC removal and 30 undergoing CVC insertion. Cancer patients self-administered the MD Anderson Symptom Inventory to rate the severity of 21 different symptoms immediately after the procedure Results : Symptoms were present in up to 57% to 67% of patients undergoing CVC insertion and removal respectively. Nineteen patients (32%) were moderately symptomatic with a symptom burden of four or more: ten insertion and nine removal patients. Symptoms with a score of 4 or more clustered around physical symptoms (pain, pressure or burning) or more generalized symptoms (fatigue, sleep, distress, dry mouth, and drowsiness). Nine (15%) patients rated at least one symptom as eight or more, five (17%) being insertion patients. Conclusions : CVCs are essential for the management of cancer patients. However, they can become infected and may need to be removed. Catheter removal and insertion produced moderate to severe symptom burden in cancer patients. Safe interventions that would salvage the vascular access without worsening the infectious outcome should be explored to alleviate morbidity associated with the symptom burden of removal and re-insertion.